Identification Of Social Capital And Intelectual Capital In Developments BUMDES In Empang Pandan Village Koto Gasib District Siak Regency - Putra Amanu (UNIVERSITAS LANCANG KUNING, 2022)
The role of social capital and intellectual capital towards the development of BUMDes in village socio economic development is an essential element that must and needs to be developed in order to spur village economic growth. Research aims : 1) Identify the social capital of BUMDesa Pandan Makmur officers, 2) Identify the intellectual capital of BUMDesa Pandan Makmur officers, 3) Identify the performance of BUMDesa Pandan Makmur officers, and 4) analyze the relationship of social capital and intellectual capital to the performance of BUMDesa Pandan Makmur officers. This research was conducted in BUMDesa Pandan Makmur in Empang Pandan Village, Koto Gasib District, Siak Regency. Social capital, intellectual capital performance of officers are measured using likert scale analysis. Qualitative descriptive analysis is used to describe the relationship of social capital and intellectual capital to officers performance. The results showed that the social capital of BUMDesa officer was formed by commitment followed by mutual respect, mutual help, values, norms, trust and participation. The intellectual capital of BUMDesa officer is formed by relational capital, structural capitan and human capital. BUMDesa employee performance is formed by work efficiency, work behavior and work effectiveness. The relationship between social capital and intellectual capital has a connection with the performance of BUMDesa employees. In terms of the development of BUMDesa Pandan Makmur for the future pay more attention to the improvement of human capital by increasing the potential of human resources or officers of BUMDesa Pandan Makmur.